Mathematical methods in image reconstruction - Natterer, F. 1941-; Wübbeling, Frank (Society for Industrial and Applied Mathematics, 2001)
This book describes the state of the art of the mathematical theory and numerical analysis of imaging. Some of the applications covered in the book include computerized tomography, magnetic resonance imaging, emission tomography, electron microscopy, ultrasound transmission tomography, industrial tomography, seismic tomography, impedance tomography, and NIR imaging.
Keywords: Image processing -- Congresses.; elektronické knihy; electronic books